Bioenergetic status and hypoxia in Lewis lung carcinoma assessed by 31P NMR spectroscopy: correlation with tumor progression - Bubnovskaya, L.; Mikhailenko, M.; Kovelskaya, A.; Osinsky, S. (Experimental Oncology, 2007)
Aim: Тo evaluate the hypoxia level and some indices of Lewis lung carcinoma energy metabolism by means of 31Р NMR spectroscopy in perchloric acid (PCA) tissue extracts during growth of primary tumor and metastasis. Мaterials and Methods: C57Bl/6 mice-bearing Lewis lung carcinoma were used in this study. Tumor energy metabolism was studied by 31P NMR spectroscopy and the metabolic NMR ratios were used as parameters for metabolic status and hypoxia level. Results: It was shown that growth of primary tumor is accompanied with increase of Pi/PCr, Pi/bNТP and PME/bNТP ratios that reflect drop of tumor energy status and oxygenation level in tumor tissue. These changes in relevant metabolic ratios correlate with enlargement of primary tumor volume (r = 0.87, p = 0.0045; r = 0.90, p = 0.0012; r = 0.764, p = 0.05, respectively) as well as with the number of lung metastases (rs = 0.761, p = 0.028; rs = 0.86, p = 0.0049; rs = 0.77, p = 0.040, respectively). Conclusion: In present study it was shown that 31Р NMR spectroscopy of PCA tumor tissue extracts may be used as reliable method for the assessment of the level of oxygenation as well as changes in energy metabolism in the experimental tumors. It may be helpful to evaluate the energy status of human tumors by investigation both of biopsy and surgical specimens. Hypoxia and hypoxia-associated metabolic events in primary tumor are linked with malignant progression, in particular metastasis. Цель: определить уровень гипоксии и некоторые показатели энергетического метаболизма карциномы легкого Льюис
с помощью 31Р ЯМР-спектроскопии перхлорных (РСА) экстрактов ткани в процессе роста первичной опухоли и ее
метастазировании. Мaтериалы и методы: использовали в исследовании мышей C57Bl/6 с перевивной карциномой легкого
Льюис. Энергетический метаболизм опухоли изучали с помощью ЯМР спектроскопии, oтношения фосфорсодержащих
метаболитов использовали в качестве параметров метаболического статуса и уровня гипоксии. Результаты: установлено,
что рост первичной опухоли сопровождается увеличением соотношений Pi/PCr, Pi/βNТP and PME/βNТP в опухоли, что
отражает снижение уровня биоэнергетического статуса и уровня оксигенации в опухоли. Эти изменения соотношений
важных метаболических показателей коррелируют с увеличением объема первичной опухоли (r = 0,87, p = 0,0045; r =
0,90, p = 0,0012; r = 0,764, p = 0,05 соответственно) и количеством метатазов в легких (rs
= 0,761, p = 0,028; rs
= 0,86,
p = 0,0049; rs
= 0,77, p = 0,040 соответственно). Выводы: установлено, что 31Р ЯМР-спектроскопия PCA тканевых
экстрактов может быть надежным методом оценки уровня оксигенации и биоэнергетического статуса экспериментальных
опухолей. Этот метод может быть полезным при оценке энергетического метаболизма опухолей человека, в частности при
исследовании биопсийного и операционного материала. Гипоксия и гипоксия-ассоциированные изменения метаболизма
в первичной опухоли связаны со злокачественной прогрессией, в частности с метастазированием.